THE EFFECT OF BRAND IMAGE AND PRODUCT QUALITY ON CONSUMER PURCHASE DECISIONS (Case Study on the ADIDAS Brand in Siman Ponorogo Sub-district) - La Ode Sugianto; Titin Eka Ardiana; Diana Pramudya Wardhani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This research is about "The Influence of Brand Image and Product Quality on Purchase Decisions (Case Study on the Adidas Brand in Siman Ponorogo Sub-District)". Researchers want to analyze and explain empirically the effect of brand image and product quality on purchasing decisions (a case study on the adidas brand in Siman PonorogoSUb-district). The type of research used in this study is associative research, namely to determine the effect or also the relationship between two or more variables. This study looks for the relationship, between the independent variables Brand Image and Product Quality on the dependent variable purchasing decisions. The research was conducted on the people of Siman District, Ponorogo Regency who use Adidas products. In this study using data collection methods in the form of a questionnaire. Questionnaire is a data collection technique that is done by giving questions or written statements to respondents to answer them. The results of this study indicate that the variables of brand image and product quality on consumer purchasing decisions simultaneously on Adidas brand shoes at the Arjuna Ponorogo Store are 54.4%. While the rest (100%-54.4% = 45.6%) is influenced by other variables outside of this study. Keywords: Brand Image, Product Quality, Purchase Decision